Analysis of Light Bulb Temperature Control for Egg Incubator Design - Che Amran, Aliza; Abdul Kadir, Ahmad Muzaffar; Zainal, Ahmad Shukri; Mohd Nor, Rozilawati; Md. Rozali, Sahazati; Mohamad Saleh, Saleha; Ahmad Hadinata Fauzi, (International Journal of Integrated Engineering, 2019)
This paper explained the analysis and findings of using light bulb as a thermal source for an incubator system. The inner dimension of the incubator is 26 cm (W) x 38 cm (L) x 26 cm (H). In the experiment, a temperature sensor that measures the inside temperature of the incubator used as a feedback signal. To run the experiments, number of light bulbs and its type were determined. There are three types of bulb used i.e. Incandescent Light (IL Bulb), Compact Fluorescent Lamp (CFL Bulb) and Light Emitting Diode (LED Bulb).  Three fixtures are proposed for each bulb type, i.e. one-bulb fixture, two-bulb fixture and three-bulb fixture. Apart from that, three control modes were tested, i.e. Mode 1, Mode 2 and Mode 3. Mode 1 is ON-OFF bulb control. Mode 2 is ON-OFF bulb control, as well as ON-OFF ventilation fan control. Finally, Mode 3 is only ON bulb control and ON-OFF ventilation fans The experimental results showed that, for the chosen incubator size, three-bulb fixture IL-type light bulb controlled with Mode 3 control gave shorter time to reach the set point then return to set point after overshoot.